PALANG PINTU PERLINTASAN KERETA API AUTOMATIS BERBASIS ARDUINO UNO - Muhammad Faisal Asyari; Sumpena Sumpena (JURNAL TEKNOLOGI INDUSTRI, 2020)
At this time the accident at the railroad crossing is still quite high, it is caused by various things, including the doorstop system which still relies on the manual system and is very vulnerable to human error such as the gate guard fatigue so late closing the doorstop, and on the design ever made previously using ultrasonic sensors still have the disadvantage that the sensor can only detect objects without being able to distinguish what objects are in front of the sensor.In this case a design or prototype of a doorstop that functions automatically based on an Arduino microcontroller can be applied to reduce the number of accidents on a railroad train and prevent detection errors on the sensor by adding a warning signal in the form of SMS. Ultrasonic sensor test results work well by detecting objects in the form of trains with a predetermined setpoint, with a working height of 4.90 volts DC for sensor 1 namely ordering the bar to close and 4.91 volts DC for sensor 2 which instructs the bar to open, for the SIM module GSM works well sending a warning signal in the form of an SMS message if there is an object blocking in the distance <= 6cm. Keywords: Arduino-Based Automatic Railway Crossing